2016
DOI: 10.1038/nplants.2016.183
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and divergence of bitterness biosynthesis and regulation in Cucurbitaceae

Abstract: Differentiation of secondary metabolite profiles in closely related plant species provide clues for unravelling biosynthetic pathways and regulatory circuits, an area that is still under-investigated. Cucurbitacins, a group of bitter and highly oxygenated tetracyclic triterpenes, are mainly produced by the plant family Cucurbitaceae. These compounds have similar structures, but differ in their anti-tumor activities and eco-physiological roles. By comparative analyses of the genomes of cucumber, melon, and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
205
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(222 citation statements)
references
References 35 publications
14
205
1
2
Order By: Relevance
“…For instance, cucurbitacin C is only found in cucumber (Panosyan et al ., ), while cucurbitacins B and E are responsible for the bitterness of melon and watermelon, respectively (Da Costa and Jones, ; Shang et al ., ). A genetic study led to the characterization of the cytochrome P450s (CYPs) in conserved synthetic loci for the cucurbitacin core skeleton, while the loss of another CYP in melon and watermelon was found to be responsible for the species‐specific accumulation of cucurbitacin C (Zhou et al ., ). Recent research revealed that variation in metabolism within a species is much larger than that had previously been thought (Luo, ), which reflects genetic diversity determining natural occurring variation in metabolites.…”
Section: The Rise Of Metabolic Diversitymentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, cucurbitacin C is only found in cucumber (Panosyan et al ., ), while cucurbitacins B and E are responsible for the bitterness of melon and watermelon, respectively (Da Costa and Jones, ; Shang et al ., ). A genetic study led to the characterization of the cytochrome P450s (CYPs) in conserved synthetic loci for the cucurbitacin core skeleton, while the loss of another CYP in melon and watermelon was found to be responsible for the species‐specific accumulation of cucurbitacin C (Zhou et al ., ). Recent research revealed that variation in metabolism within a species is much larger than that had previously been thought (Luo, ), which reflects genetic diversity determining natural occurring variation in metabolites.…”
Section: The Rise Of Metabolic Diversitymentioning
confidence: 97%
“…To identify effects of more widespread genetic variants on metabolic diversity across natural populations, mGWAS was initially applied in the model species Arabidopsis thaliana and then successfully performed in and extended to a number of other species, especially important crops. These studies covered primary metabolites (Strauch et al ., ; Angelovici et al ., ; Du et al ., ) and secondary metabolites (Dong et al ., ; Peng et al ., , ), ranging from vegetative tissue (Chen et al ., ; Matsuda et al ., ; Fang et al ., ) to reproductive tissue (Wen et al ., ; Zhou et al ., ; Zhu et al ., ). Generally, agricultural performance is under the control of numerous loci of small effects (Huang et al ., ).…”
Section: Deciphering the Genetic Bases Of Metabolic Diversity With Mgwasmentioning
confidence: 99%
“…Although plant genome data are becoming more readily available, we are still not able to predict which natural product pathways will be clustered and which will not. Moreover, although conserved gene clusters have been observed in closely related species that produce chemically similar products, it is not known how well gene clusters would be conserved in less closely related species that produce chemically divergent compounds. An example is the monoterpene indole alkaloids (MIAs), which are produced by plants of the Apocynaceae, Gelsemiaceae, Loganiaceae, Nyssaceae and Rubiaceae families.…”
Section: Figurementioning
confidence: 99%
“…For tetracyclic terpene biosynthesis, CYP81Q58, CYP87D20, CYP88L2, CYP81Q59 and CYP87D18 are able to decorate the cucurbitadienol scaffold in the production of cucurbitacins and morgrol (Shang et al ., ; Itkin et al ., ; Zhou et al ., ). These enzymes, except for CYP81Q59 and CYP88L2, are conserved across the cucurbit plants.…”
Section: Metabolic Diversity Of Plant Triterpenoidsmentioning
confidence: 97%